Activity-Based Costing’s Application in Determining Cost of Goods Manufactured at UD Barokah Jaya - Alfred Salindeho (International Journal Labs, 2021)
Increasing global competition is resulting in upheaval in every industrial and trade world, industrial or manufacturing companies demand manufacturers to be more productive and efficient to get good and cheaper products. With the intense competition between industrial companies, the company must be able to implement a good strategy so that it is able to survive the competition that occurs today. Many companies realize that the cost system in their company is inadequate to compete in the current circumstances. One consistent problem is the difference in regulating and controlling production costs. This study aims to determine the comparison of cost of goods sold (HPP) using the method applied by UD Barokah Jaya at this time with the cost of goods produced by the activity-based costing (ABC) method. The analytical method used is descriptive quantitative analysis. The results showed that the HPP calculation using ABC gave lower results than the traditional method at the UD Barokah Jaya company.